2022
DOI: 10.1021/acsapm.2c00655
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Two-Terminal Optoelectronic Synapse Based on Zinc Oxide/Poly(3-hexylthiophene) Heterojunction for Neuromorphic Computing

Abstract: With the advantages of wide bandwidth, low power consumption, high propagation speed, and excellent interconnectivity, the light-tunable synapse is regarded as one of the most promising candidates to pave the way for constructing neuromorphic computing and overcoming the von Neumann bottleneck. Herein, an optoelectronic synaptic memristor based on zinc oxide/poly(3-hexylthiophene) (ZnO/ P3HT) heterojunction is fabricated via a simple two-step spin coating process. The prepared device can simulate typical neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…The results show that the shorter the interval between two pulses, the greater the conductance change of the memristor. Besides, the PPF curve is fitted according to eq normalΔ W = ( G 2 G 1 ) / G 1 × 100 % PPF = ( G 2 G 1 ) / G 1 × 100 % = C 1 exp ( t / τ 1 ) + C 2 exp ( t / τ 2 ) where G 1 and G 2 are, respectively, the conductance values after the first and second pulses, and t is defined as the pulse interval.…”
Section: Resultsmentioning
confidence: 99%
“…The results show that the shorter the interval between two pulses, the greater the conductance change of the memristor. Besides, the PPF curve is fitted according to eq normalΔ W = ( G 2 G 1 ) / G 1 × 100 % PPF = ( G 2 G 1 ) / G 1 × 100 % = C 1 exp ( t / τ 1 ) + C 2 exp ( t / τ 2 ) where G 1 and G 2 are, respectively, the conductance values after the first and second pulses, and t is defined as the pulse interval.…”
Section: Resultsmentioning
confidence: 99%
“…Then, the trapped carriers can gradually restore the device to the initial state through detrapping behavior. [ 31,85,87–91 ]…”
Section: Categories Of Ld Optoelectronic Neuromorphic Devicesmentioning
confidence: 99%
“…Then, the trapped carriers can gradually restore the device to the initial state through detrapping behavior. [31,85,[87][88][89][90][91] Liang et al [92] reported a high-performance optoelectronic synapse transistor based on InP/ZnSe quantum dots (QDs) and n-type SnO 2 heterostructure (Figure 7a). This special heterojunction improves the separation efficiency of photoexcited charges, leading to high photoresponsivity and tunable synaptic weight changes.…”
Section: Heterojunction Channel Transistorsmentioning
confidence: 99%
“…This study effectively emulates superior visual perception and visual memory performance. Zhao et al [ 203 ] built an array using the zinc oxide/poly(3-hexylthiophene) (ZnO/P3HT) optoelectronic heterojunction memristor. Figure 12(d) shows the current attenuation of input images obtained by varying the wavelength, intensity, and frequency of the light.…”
Section: Devices Using Various Optoelectronic Materials and Their Vis...mentioning
confidence: 99%
“…(d) Input image encoded by light of different wavelengths, intensities and frequencies for ZnO/P3HT optoelectronic heterojunction memristor. Reproduced by permission from [ 203 ], copyright [2022, American Chemical Society].…”
Section: Devices Using Various Optoelectronic Materials and Their Vis...mentioning
confidence: 99%